Effectiveness of Local Institutions as The Basis of Sustainable Tourism Village - Widhianthini, Widhianthini (E-Journal of Tourism; Volume 4 Number 1 (March 2017), 2017)
The purpose of this study was to describe the institutional position of local water control system and Pakraman as policy makers in developing sustainable tourism villages. This study was conducted in Tabanan, Bali. Tabanan is a famous tourist village area with rice barns. Analytical approach through a dynamic system combined with the scoring system. The results of the study reinforced the position of local institutions such as Subak and Pakraman that collaborate to determine the sustainability of tourism villages. The local institutions act as policy makers so there is no shifting balance of nature (a decrease in agricultural land or fields). This success will be realized if the role of local institutions were legitimized through local legislation and awig awig so the model of sustainable tourism village could be directed and conserved.
Keywords: local institutions (Subak and Pakraman); tourism villages; dynamical systems; Provincial Regulations of awig awig